2014
DOI: 10.3856/vol42-issue3-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Emerita analoga (Stimpson, 1857) larvae in northern coast of Chile (25 31.5 S)

Abstract: ABSTRACT. The larvae of Emerita analoga, captured on the northern coast of Chile, during three consecutive years, during the austral summer, were separated by stage of development and their abundance, occurrence, and distribution, was analyzed for its proximity to the coast. The highest abundance was determined in coastal sampling stations and near the main sandy beaches of the study area, where the initial developmental stages were predominantly represented. The intermediate development stages proportionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Unfortunately, there are few records of the larval dynamics in E. brasiliensis. In a study with Emerita analoga (Stimpson, 1857), a closely related species on the coast of Chile, Mujica et al (2014) observed higher density of zoea I close to the adult populations in the coastal region. These authors indicated that only intermediate larval stages were found at more distant sampling spots.…”
Section: Larval Behavior Of Six Decapod Speciesmentioning
confidence: 94%
“…Unfortunately, there are few records of the larval dynamics in E. brasiliensis. In a study with Emerita analoga (Stimpson, 1857), a closely related species on the coast of Chile, Mujica et al (2014) observed higher density of zoea I close to the adult populations in the coastal region. These authors indicated that only intermediate larval stages were found at more distant sampling spots.…”
Section: Larval Behavior Of Six Decapod Speciesmentioning
confidence: 94%
“…Coquimbo Bay is part of a larger ecosystem, that researchers called "Coquimbo Bays System" (CBS) (Thiel et al 2007, Flores and Mujica 2009, Mujica et al 2014; Fig. 1) because a series of five bays occur over 100 km of shoreline: two in Tongoy (Barnes and Socos bays), Guanaqueros, La Herradura, and Coquimbo.…”
Section: Study Area and Brief Introduction To The Social-ecological System Of The Surf Clam Fishery In The Coquimbo Baymentioning
confidence: 99%
“…Acuña et al (1989) pointed out that the upwelling area in front of Fray Jorge National Park (31°S) influences the entire CBS, including islands near Punta Choros (29°25'S) allowing the confluence of waters from the south and west, which generates upwelling foci (Acuña et al 2007). Some authors (Flores & Mujica 2009, Mujica et al 2014 suggested that a larval retention place is in the northern part of the CBS, where the highest larval concentrations of other species were found. Probably a consequence of the zooplankton drift produced by the Humboldt Current interaction, flowing from south to north (Escribano et al 2002) and action of two turns caused by geostrophic circulation and the diurnal tides component, allowing waters coming from Tongoy Bay to reach the bays north of it (Acuña et al 1989).…”
mentioning
confidence: 99%